Monte-Carlo Simulation of γ-ray and Fast Neutron Radiolysis of Liquid Water and 0.4 M H2SO4 Solutions at Temperatures up to 325oC - G.R. Sunaryo; M. Jintana; JPJ. Gerin (PPIKSN-BATAN, 2011)
Monte-Carlo simulations were used to study the radiolysis of liquid water at 25-325oC when subjected to low linear energy transfer (LET) of 60Co γ-ray radiation and fast neutrons of 2 and 0.8 MeV. The energy deposited in the early stage of 60Co γ-ray irradiation was approximated by considering short segments ( 150 μm) of 300 MeV proton tracks, corresponding to an average LET of 0.3 keV/μm. In case of 2 MeV fast neutrons, the energy deposited was considered by using short segments ( 5 μm) of energy at 1.264, 0.465, 0.171, 0.063 and 0.24 MeV. 0.8 MeV fast neutrons were approximated by 0.505, 0.186, 0.069 and 0.025 MeV protons. The effect of 0.4 M H2SO4 solution on radiolysis was also studied by this method for both 60Co γ-rays and 0.8 MeV fast neutrons. The simulated results at the time of 10-7s after irradiation were obtained and compared with the available experimental results published by other researchers to be in excellent agreement with them over the entire temperature ranges and radiation sources studied. Except for g(H2) that increase with temperature rises, the general behaviors of higher radical products and lower molecular products at higher temperatures were obtained. The LET effect is also validated by this study, showing that the increase in LET would yield higher molecular and lower radical products. Studies on 0.4 M H2SO4 solutions also show good agreement between the computed and experimental data for γ-ray irrradiation: the presence of 0.4 M H+, except for g(H2) that gives lower value at 25oC and higher value at 325oC, gives the higher values for radicals and g(H2O2) at 25oC and lower values at 325oC, compared with that for neutral water. The computed data show good agreement with the experimental data for 0.4 M H2SO4 solutions induced by 0.8 MeV fast neutrons, except for g(H2) and g(H●) that gives good agreement up to 50oC, then the opposite tendencies with the further temperature rises. However, the simulated fast neutron radiolysis on acidic demonstrates similar tendencies on temperature dependence with that for simulated 60Co γ-radiolysis, but in different magnitude. For better understanding, more experimental data for fast neutrons are needed, especially under the acidic conditions. Received: 20 November 2009; Revised: 06 April 2011; Accepted: 12 April 2011